Website Quality and The Role of Customer Satisfaction Toward Repurchase Intention: A Study of Indonesian E-Commerce - Nugroho Hardiyanto; Anhari Firdaus (Politeknik Negeri Bandung, 2021)
During COVID-19 pandemic, e-commerce sector in Indonesia showed a significant rise in visitors based on the survey of Katadata. The number of visits to e-commerce websites is very high in the third quarter of 2020. Additionally, the e-commerce sector is one of the highest contributors to Indonesia’s gross domestic product (GDP). Thus, increasing consumer satisfaction and repurchase intention is essential for companies, especially in fashion products. This study aims to measure website quality on repurchase intention through the role of consumer satisfaction in the context of e-commerce in Indonesia. Furthermore, website quality has dimensions such as information quality, system quality, and e-service quality. This study uses a descriptive quantitative approach that focuses on e-commerce in Indonesia. The data is collected through an online questionnaire which is distributed to 333 consumers who used e-commerce to buy fashion products and used for further analysis. To analyze each variable, partial least squares structural equation modeling (PLS-SEM) is used to test the hypotheses. This study found that all dimensions of website quality and customer satisfaction are determining factors in repurchase intention. Then, customer satisfaction is an essential factor to encourage repurchase intention in website quality. This study extends our understanding of website quality theory in the e-commerce context.